Employing an IL-23 p19 vaccine to block IL-23 ameliorates chronic murine colitis. (December 2013) - Guan, Qingdong; Burtnick, Helen A; Qing, Gefei; Weiss, Carolyn R; Ma, Allan G; Ma, Yanbing; Warrington, Richard J; Peng, Zhikang
Background: Overexpression of IL-23 has been implicated in the pathogenesis of Crohn's disease. Using vaccines to block overexpressed endogenous cytokines has emerged as a new therapeutic strategy for the long-term treatment of the disease. Aim: We sought to develop peptide-based vaccines specific to IL-23 and evaluate their effects in colitis mice.Materials & methods: The vaccine was developed by inserting a peptide derived from mouse IL-23 p19 into the carrier protein, hepatitis B core antigen, using molecular engineering methods. One vaccine against IL-23 p19 was obtained that induced high-titered and long-lasting antibodies to IL-23 without the use of adjuvants. The inhibitory effect of vaccine-immunized serum was subsequently evaluated in vitro . To evaluate the in vivo effects, mice were subcutaneously injected with the vaccine, carrier or saline three times. Two weeks after the last injection, chronic colitis was induced in mice by seven weekly administrations with 2, 4, 6-trinitrobenzene sulfonic acid.Results: In vitro studies revealed that serum IL-23 p19-specific IgG significantly suppressed IL-23-induced IL-17 production by splenocytes. In vivo evaluation of the effect of the vaccine in mice with chronic colitis indicated that vaccine-immunized mice exhibited a decrease in colon inflammation, collagen deposition and levels of IL-23 and IL-12 cytokines, compared with control groups.Conclusion: IL-23 p19 vaccine is capable of downregulating inflammatory responses in chronic murine colitis, providing a novel therapeutic approach in Crohn's disease.